Knowledge of Game Rules and Speed on The Performance of South Sulawesi Association Football Referees - Suwardi; Sudiadharma; Nurussyariah; Hudain, Muh. Adnan; Jamaluddin, Juniarto (Education and Talent Development Center Indonesia (ETDC Indonesia), 2024)
This study aims to examine the correlation between knowledge of game rules and physical condition and the performance of football referees in the South Sulawesi provincial association. The research population consisted of football referees from the South Sulawesi provincial association. A sample of 30 people was taken based on purposive sampling. The referee's performance was the dependent variable of the study, whereas knowledge of game rules and physical condition were the independent variables. The research method employed a descriptive approach. The research data were analyzed using correlational techniques at a 95% significance level. The results of the study reveal that: (1) there is a significant correlation between knowledge of game rules and referee’s performance with a correlation value (r) of 0.746 and a contribution of 55.6%; (2) there is a significant correlation between the referee's physical condition and the referee's performance with a correlation value (r) of 0.751 and a contribution of 56.4%; and (3) there is a correlation between knowledge of game rules and physical condition collectively on referee’s performance with a correlation value (r) of 0.824 and a contribution of 68.4%.